Assembly factors and ATP-dependent proteases in cytochrome c oxidase biogenesis - Stiburek, Lukas; Zeman, Jiri (Biochimica et biophysica acta, 2010)
Eukaryotic cytochrome c oxidase (CcO), the terminal enzyme of the energy-transducing mitochondrial electron transport chain is a hetero-oligomeric, heme-copper oxidase complex composed of both mitochondrially and nuclear-encoded subunits. It is embedded in the inner mitochondrial membrane where it couples the transfer of electrons from reduced cytochrome c to molecular oxygen with vectorial proton translocation across the membrane. The biogenesis of CcO is a complicated sequential process that requires numerous specific accessory proteins, so-called assembly factors, which include translational activators, translocases, molecular chaperones, copper metallochaperones and heme a biosynthetic enzymes. Besides these CcO-specific protein factors, the correct biogenesis of CcO requires an even greater number of proteins with much broader substrate specificities. Indeed, growing evidence indicates that mitochondrial ATP-dependent proteases might play an important role in CcO biogenesis. Out of the four identified energy-dependent mitochondrial proteases, three were shown to be directly involved in proteolysis of CcO subunits. In addition to their well-established protein-quality control function these oligomeric proteolytic complexes with chaperone-like activities may function as molecular chaperones promoting productive folding and assembly of subunit proteins. In this review, we summarize the current knowledge of the functional involvement of eukaryotic CcO-specific assembly factors and highlight the possible significance for CcO biogenesis of mitochondrial ATP-dependent proteases.
Keywords: Saccharomyces cerevisiae; Animals; molekulární chaperony; ATP-Dependent Proteases; Molecular Chaperones; mitochondrie; lidé; Electron Transport Complex IV; podjednotky proteinů; Models, Biological; Protein Subunits; Mitochondria; Humans; biologické modely; zvířata; respirační komplex IV; proteasy závislé na ATP